Electrolyte, battery and electric equipment
High ionic conductivity is formed by using an electrolyte containing 2,3-dihydropyridino[2,3-d][1,3]azole-2-one and tris(trimethylsilane) phosphate in a battery The SEI film with thermal stability solves the problem of SEI film decomposition in high temperature environments and improves the energy efficiency and safety performance of the battery.
Patent Information
- Application Number
- CN202411650027.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-14
AI Technical Summary
In high temperature environments, solid electrolyte interface mask (SEI film) is prone to decomposition or structural damage, resulting in increased internal resistance of the battery, rapid attenuation of capacity, and may cause safety problems such as thermal runaway.
An electrolyte is used, which comprises the first additive 2,3-dihydropyridino[2,3-d][1,3]azole-2-one and the second additive tri(trimethylsilane)phosphate ester. These additives work together to form an SEI film with high ionic conductivity and thermal stability, reducing the intercalation or removal impedance of lithium ions and improving the stability of the SEI film.
By forming a stable SEI film, the internal resistance of the battery under high temperature conditions is reduced, the rapid attenuation of capacity is avoided, and the energy efficiency, circulation performance and safety performance of the battery are improved.
Smart Images

Figure CN119447462A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to an electrolyte, a battery and an electrical device. Background Art
[0002] With the continuous development of battery technology, higher requirements are placed on the high-temperature cycle of batteries. In batteries, the solid electrolyte interphase (SEI) membrane plays a vital protective role in the working process of the battery. It can prevent the electrolyte from directly contacting the electrode, thereby reducing side reactions. However, in a high-temperature environment, the SEI membrane is prone to decomposition or structural damage, resulting in increased internal resistance of the battery, rapid capacity decay, and even safety issues such as thermal runaway. Summary of the invention
[0003] In view of this, the present application provides an electrolyte, a battery and an electrical device. When the electrolyte is applied to the battery, the battery has higher energy efficiency, better cycle performance and safety performance.
[0004] The present application provides an electrolyte, which includes a first additive and a second additive, wherein the first additive includes 2,3-dihydropyrido[2,3-d][1,3]oxazol-2-one, and the second additive includes tris(trimethylsilyl)phosphate.
[0005] Furthermore, in the electrolyte, the mass fraction of the first additive is a, and the mass fraction of the second additive is b, then the relationship is satisfied: 0.4≤b / a≤4.
[0006] Furthermore, the mass fraction a of the first additive is in the range of 0.1%≤a≤5%.
[0007] Furthermore, in the electrolyte, the mass fraction b of the second additive is in the range of 0.1%≤b≤5%.
[0008] The present application also provides a battery, which includes: an electrode assembly and an electrolyte provided by the present application, wherein the electrode assembly includes a stacked negative electrode plate, a separator and a positive electrode plate, and the positive electrode plate includes a stacked current collector layer and an active material layer; the electrolyte is used to infiltrate at least a portion of the electrode assembly.
[0009] Furthermore, the active material layer includes LiM x Fe (1-x) PO4, wherein M is selected from at least one of vanadium, titanium, magnesium, manganese, aluminum and molybdenum, and the range of x is: 0.005≤x≤0.05.
[0010] Furthermore, in the electrolyte, the mass fraction of the first additive is a, and the battery satisfies the relationship: 0.2≤a / x≤1.
[0011] Furthermore, the diaphragm includes a base film and a coating layer which are stacked, the coating layer is a ceramic coating and the thickness D of the coating layer satisfies the range: 2.5 μm≤D≤3.5 μm.
[0012] Furthermore, the coating has pores, and the porosity α of the coating is in the range of 35%≤α≤65%.
[0013] The present application provides an electrical device, which includes: a device body and a battery provided in the present application, wherein the battery supplies power to the device body.
[0014] In the present application, the electrolyte includes a first additive, and the first additive includes 2,3-dihydropyrido[2,3-d][1,3]oxazol-2-one, the first additive includes a five-membered heterocyclic ring and has a nitrogen atom on the ring. Compared with other chain structures, the first additive is easy to open the ring and separate the nitrogen atom, and the free nitrogen reacts with the lithium ions in the electrolyte to form a solid electrolyte interface film (SEI film) with lithium nitride on the surface of the negative electrode plate. The SEI film containing nitrogen has a higher ionic conductivity to reduce the impedance of lithium ions embedded in or out of the negative electrode plate through the SEI film, thereby accelerating the diffusion rate of lithium ions in the battery, preventing active lithium from being consumed, and reducing the generation of heat, so that the SEI film containing nitrogen also has a higher thermal stability, which is beneficial to improve the high temperature performance of the battery when the electrolyte is applied to the battery. Further, the proton hydrogen of nitrogen on the five-membered heterocyclic ring of the first additive is easy to fall off and form hydrogen fluoride to attack the SEI film of the first additive, and the electrolyte also includes a second additive, the second additive includes tris (trimethylsilane) phosphate, and the second additive can be combined with the proton hydrogen of the first additive to form trimethylfluorosilane to avoid the generation of hydrogen fluoride, thereby further improving the stability of the SEI film formed by the first additive. Furthermore, the phosphate group of the second additive can also form a product with lithium ions in the electrolyte, which is beneficial to increase the thickness of the SEI film, thereby further improving the stability of the SEI film. The electrolyte of the present application has a good stability through the synergistic effect of the first additive and the second additive, so as to avoid decomposition or structural damage of the SEI film, reduce the consumption of active lithium in the electrolyte, reduce the internal resistance of the battery under high temperature conditions, and avoid the attenuation of the battery capacity, so that when the electrolyte is applied to the battery, the battery has higher energy efficiency, better cycle performance and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the implementation will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0016] Figure 1 A schematic diagram of the structure of a battery according to an embodiment of the present application;
[0017] Figure 2 A schematic cross-sectional structure diagram of a positive electrode sheet according to an embodiment of the present application;
[0018] Figure 3 A schematic diagram of the cross-sectional structure of a diaphragm according to an embodiment of the present application;
[0019] Figure 4 A circuit block diagram of an electrical device according to an embodiment of the present application;
[0020] Figure 5 This is a schematic diagram of the structure of an electrical device according to an embodiment of the present application.
[0021] Description of reference numerals:
[0022] 100 - battery, 110 - electrode assembly, 111 - negative electrode plate, 112 - separator, 1121 - base film, 1122 - coating, 113 - positive electrode plate, 1131 - current collector layer, 1132 - active material layer, 120 - electrolyte, 200 - electrical equipment, 210 - equipment body. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0024] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.
[0025] Reference to "embodiment" or "implementation" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment or implementation may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0026] With the continuous development of battery technology, higher requirements are placed on the high-temperature cycle of batteries. Traditional energy storage batteries are prone to problems such as rapid capacity decay, increased internal resistance, and decreased charge and discharge efficiency in high-temperature environments, which seriously affect the performance and service life of the energy storage system. In the battery, the solid electrolyte interphase (SEI) membrane plays a vital protective role in the operation of the battery. It prevents direct contact between the electrolyte and the electrode, thereby reducing side reactions. However, in a high-temperature environment, the SEI membrane is prone to decomposition or structural damage, resulting in increased internal resistance of the battery, rapid capacity decay, and even safety issues such as thermal runaway.
[0027] High temperature will cause the electrolyte inside the battery to decompose and the stability of the SEI film to decrease, thereby increasing the internal resistance of the battery. Increased internal resistance will reduce the energy efficiency of the battery, resulting in increased heat generation of the battery, forming a vicious cycle. Secondly, in lithium-ion batteries, since the ionic conductivity of lithium iron phosphate batteries themselves is not high, doped lithium iron phosphate is usually used to improve energy efficiency, but SEI is not stable enough at high temperatures, and lithium ions diffused from the positive electrode will be over-consumed, increasing capacity attenuation. Finally, in a high temperature environment, repairing the ruptured SEI film will increase impedance, and the increase in impedance will increase heat generation. The local temperature hotspots inside the battery cell will cause the SEI film to rupture again, and this will form a vicious cycle.
[0028] See also Figure 1 The present application provides an electrolyte 120, wherein the electrolyte 120 includes a first additive and a second additive, wherein the first additive includes 2,3-dihydropyrido[2,3-d][1,3]oxazol-2-one, and the second additive includes tris(trimethylsilyl)phosphate.
[0029] It can be understood that the structural formula of 2,3-dihydropyrido[2,3-d][1,3]oxazol-2-one is:
[0030] It can be understood that the electrolyte 120 is applied to the battery 100 , the battery 100 includes a negative electrode plate 111 , the electrolyte 120 is used to soak the negative electrode plate 111 , and the electrolyte 120 also includes free lithium ions.
[0031] In this embodiment, the electrolyte 120 includes a first additive, and the first additive includes 2,3-dihydropyrido[2,3-d][1,3]oxazol-2-one, and the first additive includes a five-membered heterocyclic ring with a nitrogen atom on the ring. Compared with other chain structures, the first additive is easy to open the ring and separate the nitrogen atom, and the free nitrogen reacts with the lithium ions in the electrolyte 120, and forms a solid electrolyte interface film (SEI film) with lithium nitride on the surface of the negative electrode plate 111. The SEI film containing nitrogen has a higher ionic conductivity to reduce the impedance of lithium ions being embedded in or out of the negative electrode plate 111 through the SEI film, thereby accelerating the diffusion rate of lithium ions in the battery 100, preventing the active lithium from being consumed, and reducing the generation of heat, so that the SEI film containing nitrogen also has a higher thermal stability, which is beneficial to improving the high temperature performance of the battery 100 when the electrolyte 120 is applied to the battery 100. Furthermore, the proton hydrogen of nitrogen on the five-membered heterocyclic ring of the first additive is easy to fall off and form hydrogen fluoride to attack the SEI film of the first additive, and the electrolyte 120 also includes a second additive, the second additive includes tris (trimethylsilyl) phosphate, and the second additive can be combined with the proton hydrogen of the first additive to form trimethyl fluorosilane to avoid the generation of hydrogen fluoride, thereby further improving the stability of the SEI film formed by the first additive. Furthermore, the phosphate group of the second additive can also form a product with the lithium ions in the electrolyte 120, which is conducive to increasing the thickness of the SEI film, thereby further improving the stability of the SEI film. The electrolyte 120 of this embodiment uses the synergistic effect of the first additive and the second additive to ensure that the SEI film formed by the first additive on the surface of the negative electrode plate 111 has good stability, thereby avoiding decomposition or structural damage of the SEI film, reducing the consumption of active lithium in the electrolyte 120, reducing the internal resistance of the battery 100 under high temperature conditions, and avoiding the attenuation of the capacity of the battery 100. Therefore, when the electrolyte 120 is applied to the battery 100, the battery 100 has higher energy efficiency, better cycle performance and safety performance.
[0032] Optionally, the ionic conductivity of the SEI film having lithium nitride formed by the first additive on the surface of the negative electrode plate 111 is in the range of 10 -7 S cm -1 Up to 10 -8 S cm -1 The SEI film formed by the first additive on the surface of the negative electrode plate 111 has a high ionic conductivity.
[0033] In some embodiments, in the electrolyte 120 , the mass fraction of the first additive is a, and the mass fraction of the second additive is b, and then the relationship is satisfied: 0.4≤b / a≤4.
[0034] Specifically, the value of b / a can be, but is not limited to, 0.4, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8 and 4, etc.
[0035] It can be understood that in the electrolyte 120 , the mass fraction of the first additive is the sum of the mass of the first additive and the mass of the electrolyte 120 .
[0036] It can be understood that, in the electrolyte 120 , the mass fraction of the second additive is the sum of the mass of the second additive and the mass of the electrolyte 120 .
[0037] In the electrolyte 120 provided in this embodiment, when the mass fraction a of the first additive and the mass fraction b of the second additive satisfy the relationship 0.4≤b / a≤4, the mass fraction of the first additive and the mass fraction of the second additive are within a reasonable range. On the one hand, the first additive can separate an appropriate amount of nitrogen atoms in the electrolyte 120, and form a complete, thermally stable and highly ionic conductive SEI film on the surface of the negative electrode plate 111 to reduce the impedance of lithium ions being embedded in or out of the negative electrode plate 111 through the SEI film, thereby accelerating the diffusion rate of lithium ions in the battery 100, preventing active lithium from being consumed, and reducing the generation of heat, and ultimately making the battery 100 have better high temperature performance when the electrolyte 120 is applied to the battery 100. On the other hand, the second additive can combine with the proton hydrogen of the first additive to form trimethylfluorosilane to avoid the generation of hydrogen fluoride, thereby further improving the stability of the SEI film formed by the first additive. The first additive and the second additive cooperate with each other to avoid decomposition or structural damage of the SEI film, reduce the consumption of active lithium in the electrolyte 120, reduce the internal resistance of the battery 100 under high temperature conditions, and avoid the attenuation of the capacity of the battery 100, so that when the electrolyte 120 is applied to the battery 100, the battery 100 has higher energy efficiency, better cycle performance and safety performance. When the value of b / a is too large, the mass fraction of the second additive is too large or the mass fraction of the first additive is too small. If the mass fraction of the second additive is too large, it may inhibit the first additive from forming a SEI film on the surface of the negative electrode plate 111, resulting in the first additive being unable to form a stable and complete SEI film on the surface of the negative electrode plate 111, thereby reducing the stability of the electrolyte 120 under high temperature conditions; if the mass fraction of the first additive is too small, the nitrogen atoms separated by the first additive are small, so that it is difficult for the first additive to form a complete and thermally stable SEI film on the surface of the negative electrode plate 111. When the electrolyte 120 is applied to the battery 100 and is subjected to high-temperature charge and discharge cycles, the SEI film is easily damaged and consumes more active lithium ions, and increases the internal resistance and heat generation of the battery 100, thereby making the energy efficiency of the battery 100 low and the safety performance poor. When the value of b / a is too small, the mass fraction of the second additive is too small or the mass fraction of the first additive is too large. If the mass fraction of the second additive is too small, the second additive cannot fully combine with the proton hydrogen detached from the first additive, and part of the proton hydrogen may react with the electrolyte 120 to generate hydrogen fluoride, and attack the SEI film formed by the first additive, reducing the structural stability of the solid electrolyte interface film.If the mass fraction of the first additive is too large, the thickness of the SEI film formed by the first additive on the surface of the negative electrode plate 111 is too large, which increases the resistance of lithium ions in the electrolyte 120 to embed or escape from the SEI film, thereby causing the internal impedance of the battery 100 and generating more heat, affecting the charging and discharging efficiency of the battery 100 and reducing the safety performance of the battery 100.
[0038] Preferably, the value of b / a satisfies the range: 1≤b / a≤3.
[0039] In some embodiments, the mass fraction a of the first additive is in the range of 0.1%≤a≤5%.
[0040] Specifically, the mass fraction a of the first additive may be, but is not limited to, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.9%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8% and 5%, etc.
[0041] In this embodiment, when the mass fraction a of the first additive satisfies the range of 0.1%≤a≤5%, the mass fraction of the first additive is within a reasonable range, the first additive can separate an appropriate amount of nitrogen atoms in the electrolyte 120, and form a complete and thermally stable SEI film on the surface of the negative electrode plate 111, and the SEI film containing lithium nitride has a high ionic conductivity to reduce the impedance of lithium ions being embedded in or out of the negative electrode plate 111 through the SEI film, thereby accelerating the diffusion rate of lithium ions in the battery 100, preventing active lithium from being consumed, and reducing the generation of heat, and ultimately making the battery 100 have better high temperature performance when the electrolyte 120 is applied to the battery 100. When the mass fraction of the first additive is too large, the thickness of the SEI film formed by the first additive on the surface of the negative electrode plate 111 is too large, which increases the resistance of lithium ions in the electrolyte 120 to embed or escape from the SEI film, thereby causing the internal impedance of the battery 100 and generating more heat, affecting the charge and discharge efficiency of the battery 100 and reducing the safety performance of the battery 100. When the mass fraction of the first additive is too small, the nitrogen atoms separated by the first additive are relatively small, so that it is difficult for the first additive to form a complete and thermally stable SEI film on the surface of the negative electrode plate 111. When the electrolyte 120 is applied to the battery 100 and is subjected to high-temperature charge and discharge cycles, the SEI film is easily damaged and consumes more active lithium ions, and increases the internal resistance and heat generation of the battery 100, thereby causing the battery 100 to have low energy efficiency and poor safety performance.
[0042] Preferably, the mass fraction a of the first additive is in the range of 0.1%≤a≤3%. Specifically, the mass fraction a of the first additive may be, but is not limited to, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.9%, 3%, etc.
[0043] In some embodiments, in the electrolyte 120 , the mass fraction b of the second additive is in the range of 0.1%≤b≤5%.
[0044] Specifically, the mass fraction b of the second additive can be, but is not limited to, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.9%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.7%, 4.9% and 5%, etc.
[0045] In this embodiment, when the mass fraction b of the second additive satisfies the range of 0.1%≤b≤5%, the mass fraction of the second additive is within a reasonable range. On the one hand, it can be avoided that the first additive is affected by the excessive mass content of the second additive to form a SEI film with thermal stability on the surface of the negative electrode plate 111; on the other hand, the second additive can combine with the proton hydrogen shed from the first additive to form tris(trimethylsilyl)phosphate, so as to avoid the proton hydrogen shed from the first additive to form hydrogen fluoride and attack the SEI film, improve the stability of the SEI film, avoid consuming the active lithium ions in the electrolyte 120, and thus improve the thermal stability, energy efficiency and cycle performance of the battery 100 when the electrolyte 120 is applied to the battery 100. When the mass fraction of the second additive is too large, the mass content of the second additive is too much, which may inhibit the first additive from forming a SEI film on the surface of the negative electrode plate 111, resulting in the first additive being unable to form a stable and complete SEI film on the surface of the negative electrode plate 111, thereby reducing the stability of the electrolyte 120 under high temperature conditions. In addition, in order to repair the damaged SEI film, the active lithium ions in the electrolyte 120 will be consumed, thereby causing the capacity of the battery 100 to decay and shortening the cycle life of the battery 100. When the mass fraction of the second additive is too small, the mass content of the second additive is too small, so that the proton hydrogen detached from the first additive cannot be fully combined, and part of the proton hydrogen may react with the electrolyte 120 to generate hydrogen fluoride, thereby attacking the SEI film formed by the first additive, reducing the structural stability of the solid electrolyte interface film, and thus reducing the high temperature performance of the battery 100 when the electrolyte 120 is applied to the battery 100.
[0046] Preferably, the mass fraction b of the second additive is in the range of 0.1%≤b≤3%.
[0047] Please also see Figure 2 The present application also provides a battery 100, which includes: an electrode assembly 110 and an electrolyte 120 provided in the present application, wherein the electrode assembly 110 includes a stacked negative electrode plate 111, a separator 112 and a positive electrode plate 113, and the positive electrode plate 113 includes a stacked current collector layer 1131 and an active material layer 1132; the electrolyte 120 is used to infiltrate at least a portion of the electrode assembly 110.
[0048] Optionally, the battery 100 may be a circular battery 100 , a square battery 100 , a soft-pack battery 100 , or the like.
[0049] Optionally, in some embodiments, the battery 100 is a lithium-ion battery.
[0050] In this embodiment, the battery 100 includes the electrolyte 120 provided in the present application, and the electrolyte 120 includes a first additive and a second additive, and the first additive and the second additive cooperate to form a SEI film with good thermal stability, high ionic conductivity and good structural stability on the surface of the negative electrode plate 111, so that the battery 100 has good cycle performance under high temperature conditions, avoiding the consumption of excessive active lithium ions in the electrolyte 120 due to damage to the SEI film, so that the battery 100 of the present application has higher energy efficiency, better cycle performance and safety performance.
[0051] In some embodiments, the active material layer 1132 includes LiM x Fe (1-x) PO4, wherein M is selected from at least one of vanadium, titanium, magnesium, manganese, aluminum and molybdenum, and the range of x is: 0.005≤x≤0.05.
[0052] Specifically, the value of x may be, but is not limited to, 0.005, 0.008, 0.009, 0.01, 0.015, 0.018, 0.02, 0.025, 0.028, 0.03, 0.034, 0.038, 0.04, 0.042, 0.045, 0.048, and 0.05, etc.
[0053] It can be understood that x can represent the amount of doping elements in lithium iron phosphate.
[0054] In this embodiment, the lithium iron phosphate in the active material layer 1132 is doped with at least one of vanadium, titanium, magnesium, manganese, aluminum and molybdenum, which can effectively improve the efficiency of lithium ion embedding or extraction from the active material layer 1132, so as to improve the diffusion efficiency of lithium ions. Based on the SEI film formed on the surface of the negative electrode plate 111 by the first additive and the second additive, the lithium ions extracted from the active material layer 1132 can quickly enter the negative electrode plate 111 through the SEI film on the surface of the negative electrode plate 111, which can avoid excessive consumption of active lithium ions. The electrolyte 120 and the active material layer 1132 cooperate with each other so that the electrolyte 120 has both high energy efficiency and good cycle performance. When x satisfies the range of 0.005≤x≤0.05, in the LiM x Fe (1-x) In PO4, the amount of doping elements is within a reasonable range, the efficiency of the lithium ions embedded in or out of the positive electrode sheet 113 is within a reasonable range, so that the amount of lithium ions diffused from the active material layer 1132 is within a reasonable range, the lithium ions can be quickly embedded in or out of the SEI film, and the excessive loss of the lithium ions can be avoided, so that the battery 100 has both high energy efficiency and good high temperature performance and cycle performance. When the value of x is too large, in LiM x Fe (1-x) In PO4, the amount of doping elements is too much, so that the efficiency of lithium ion embedding or extraction from the positive electrode sheet 113 is too high. Accordingly, too many lithium ions diffused from the active material layer 1132 are over-consumed, thereby reducing the amount of reversible lithium ions in the battery 100 and ultimately reducing the capacity retention rate of the battery 100. When the value of x is too small, in LiM x Fe (1-x) In PO4, the amount of doping elements is too small, which makes the efficiency of lithium ions embedding or escaping from the positive electrode plate 113 low. In other words, the resistance of the lithium ions to escape from the active material layer 1132 is large. Accordingly, the number of lithium ions diffused from the active material layer 1132 is too small. Even if the SEI film formed by the first additive and the second additive on the surface of the negative electrode plate 111 has a high ionic conductivity, it is difficult to improve the energy efficiency of the battery 100.
[0055] In some embodiments, in the electrolyte 120 , the mass fraction of the first additive is a, and the battery 100 satisfies the relationship: 0.2≤a / x≤1.
[0056] Specifically, the value of a / x can be, but is not limited to, 0.2, 0.25, 0.28, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.63, 0.69, 0.7, 0.72, 0.75, 0.78, 0.8, 0.82, 0.85, 0.89, 0.9, 0.91, 0.95 and 1, etc.
[0057] In this embodiment, when the battery 100 satisfies the relationship 0.2≤a / x≤1, the mass fraction of the first additive and the amount of doping elements in the active material layer 1132 are within a reasonable range. On the one hand, the amount of nitrogen atoms separated by the first additive is within a reasonable range and forms a complete SEI film with high electrical conductivity and high thermal stability on the surface of the negative electrode plate 111; on the other hand, the amount of lithium ions diffused from the active material layer 1132 is within a reasonable range. The first additive and the active material layer 1132 cooperate with each other to make full use of the SEI film with high electrical conductivity, thereby improving the energy efficiency of the battery 100 while improving the cycle performance of the battery 100 at high temperature. When the value of a / x is too large, the mass fraction of the first additive is too large, or the amount of the doping element in the lithium iron phosphate is too small, and the thickness of the SEI film formed by the first additive on the surface of the negative electrode plate 111 is too large, which increases the resistance of lithium ions in the electrolyte 120 to be embedded in or removed from the SEI film, and the amount of lithium ions diffused from the active material layer 1132 is too small, so that the energy efficiency of the battery 100 is low and the cycle performance is poor. When the value of a / x is too small, the mass fraction of the first additive is too small, or the amount of the doping element in the lithium iron phosphate is too large. If the mass fraction of the first additive is too small, the nitrogen atoms separated by the first additive are small, so that the first additive is difficult to form a complete and thermally stable SEI film on the surface of the negative electrode plate 111, which reduces the cycle performance of the battery 100 at high temperature. If the amount of doping elements in the lithium iron phosphate is too much, the efficiency of lithium ion embedding or extraction from the positive electrode plate 113 is too high. Accordingly, too many lithium ions diffuse from the active material layer 1132 and are over-consumed, thereby reducing the amount of reversible lithium ions in the battery 100 and ultimately reducing the capacity retention rate of the battery 100.
[0058] Please also see Figure 3 In some embodiments, the diaphragm 112 includes a base film 1121 and a coating 1122 which are stacked, the coating 1122 is a ceramic coating 1122 and the thickness D of the coating 1122 satisfies the range: 2.5 μm ≤ D ≤ 3.5 μm.
[0059] Specifically, the thickness D of the coating 1122 may be, but is not limited to, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, etc.
[0060] It can be understood that the coating layer 1122 is coated on the surface of the base film 1121 .
[0061] Optionally, in some embodiments, the base film 1121 is a polyethylene base film 1121 .
[0062] In this embodiment, the diaphragm 112 includes a stacked base film 1121 and a coating 1122, and the coating 1122 is a ceramic coating 1122. When the thickness of the coating 1122 is within a reasonable range, the diaphragm 112 has higher thermal conductivity and higher ionic conductivity than the traditional polypropylene diaphragm 112. During the charge and discharge process of the battery 100, the diaphragm 112 can effectively transfer the heat generated by the electrode assembly 110 to the outside to avoid the problem of thermal runaway caused by excessive heat inside the battery 100, further improving the safety performance of the battery 100. In addition, the ceramic coating 1122 has more pores, and the diaphragm 112 has a higher ionic conductivity, which is conducive to improving the diffusion efficiency of lithium ions, thereby reducing the impedance inside the battery 100, and then helping to improve the energy efficiency and cycle performance of the battery 100.
[0063] Optionally, the porosity of the base film 1121 ranges from 35% to 50%. Specifically, the porosity of the base film 1121 may be, but is not limited to, 35%, 36%, 38%, 40%, 42%, 45%, 46%, 47%, 48%, 49%, 50%, etc.
[0064] In some embodiments, the coating 1122 has pores, and the porosity α of the coating 1122 is in the range of 35%≤α≤65%.
[0065] Specifically, the porosity α of the coating 1122 can be, but is not limited to, 35%, 38%, 39%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 56%, 58%, 60%, 62%, 64% and 65%, etc.
[0066] In this embodiment, when the porosity α of the coating 1122 satisfies the range of 35%≤α≤65%, the porosity of the coating 1122 is within a reasonable range, which is conducive to reducing the impedance of lithium ions in the electrolyte 120 passing through the diaphragm 112, thereby improving the diffusion efficiency of lithium ions, and then making the battery 100 have higher energy efficiency and cycle performance. When the porosity of the coating 1122 is too large, it may cause the positive electrode plate 113 to directly contact the negative electrode plate 111 and cause a short circuit, thereby reducing the safety performance of the battery 100. With the increase of doping elements in the active material layer 1132, the number of lithium ions released from the active material layer 1132 increases. When the porosity of the coating 1122 is too small, the difficulty and impedance of the lithium ions embedded in or released from the diaphragm 112 increase, which may cause more lithium ion loss and reduce the energy efficiency of the battery 100.
[0067] Optionally, in some embodiments, the coating 1122 is a boehmite coating.
[0068] It can be understood that boehmite is also called diaspore, and its molecular formula is γ-AlOOH, that is, hydrated aluminum oxide.
[0069] In this embodiment, the coating 1122 is a boehmite coating, and the coating 1122 includes hydrated alumina so that the coating 1122 has a hydroxyl group (-OH). When the diaphragm 112 and the first additive are used in combination, the proton hydrogen on the five-membered heterocyclic ring of the first additive is easily combined with the hydroxyl group due to the action of hydrogen bonds, so that the first additive is easily adsorbed on the surface of the coating 1122. The nitrogen atoms in the first additive contain lone pairs of electrons, which can attract lithium ions in the electrolyte 120 and allow the lithium ions to pass through the diaphragm 112 quickly, so as to reduce the impedance of the lithium ions passing through the diaphragm 112, thereby improving the energy efficiency of the battery 100.
[0070] Optionally, the coating 1122 is a ceramic coating having relatively more pores.
[0071] The technical solution of this application is further introduced in the following with multiple embodiments:
[0072] Example 1 to Example 8, Comparative Example 1 to Comparative Example 9:
[0073] 1. Preparation of electrolyte 120:
[0074] In an argon atmosphere glove box with a moisture and oxygen content of ≤0.01ppm, ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) are mixed uniformly in a mass ratio of 1:2:1 to form a solvent; then the dried electrolyte lithium hexafluorophosphate is dissolved in the solvent and stirred until completely dissolved; finally, the first additive and the second additive are added and mixed uniformly again to obtain the electrolyte 120 of Examples 1 to 8 and Comparative Examples 1 to 9.
[0075] Among them, the first additive includes 2,3-dihydropyrido[2,3-d][1,3]oxazol-2-one, and the second additive includes tris(trimethylsilyl)phosphate. In the electrolyte 120 of Examples 1 to 10 and Comparative Examples 1 to 9, the mass fraction a of the first additive, the mass fraction b of the second additive, and the value of b / a are as shown in Table 1.
[0076] 2. Preparation of electrode assembly 110:
[0077] (1) Preparation of positive electrode sheet 113:
[0078] The positive electrode active material LiM x Fe (1-x) PO4, positive electrode conductive agent conductive carbon black (Super-P), positive electrode binder polyvinylidene fluoride PVDF are mixed in a mass ratio of 94:3:3; then nitrogen-methyl pyrrolidone (NMP) is added as a solvent to prepare a positive electrode slurry with a solid content of 60%, and stirred evenly, and then the positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10 μm, and then dried, cold pressed, slit, and cut to form an active material layer 1132 to obtain a positive electrode sheet 113. Among them, the positive electrode active material LiM in Examples 1 to 8 and Comparative Examples 1 to 9 is x Fe (1-x) In PO4, the values of x and a / x are shown in Table 1.
[0079] (2) Preparation of negative electrode sheet 111:
[0080] The negative electrode active material artificial graphite, the negative electrode thickener sodium carboxymethyl cellulose (CMC), the negative electrode conductive agent conductive carbon black (Super-P) and the negative electrode binder styrene butadiene rubber latex (SBR) are mixed in a mass ratio of 96:2:1:1, deionized water is added, and the negative electrode slurry with a solid content of 50% is prepared and stirred evenly. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6 μm, and after drying, cold pressing, slitting and cutting, a negative electrode active layer is formed to obtain a negative electrode sheet 111.
[0081] (3) Preparation of diaphragm 112:
[0082] A polyethylene base film 1121 is used as the base film 1121 , and a ceramic coating 1122 is coated on the surface of the base film 1121 .
[0083] The positive electrode sheet 113 , the separator 112 , and the negative electrode sheet 111 are stacked and then wound into a bare cell to form the electrode assembly 110 of Examples 1 to 8 and Comparative Examples 1 to 9.
[0084] 3. Assembly of battery 100:
[0085] The electrode assembly 110 is placed in a shell, and after drying, the above-mentioned electrolyte 120 is injected. After vacuum packaging, standing, forming, shaping, etc., implementation batteries 1 to implementation batteries 8 and comparison batteries 1 to comparison batteries 9 are finally prepared, wherein implementation battery 1 includes the electrolyte 120 and electrode assembly 110 of Example 1, implementation battery 2 includes the electrolyte 120 and electrode assembly 110 of Example 2, comparison battery 1 includes the electrolyte 120 and electrode assembly 110 of comparison example 1, comparison battery 2 includes the electrolyte 120 and electrode assembly 110 of comparison example 2, and so on.
[0086] Table 1: Component parameters of the electrolyte 120 of Examples 1 to 8 and Comparative Examples 1 to 9, and structural parameters of Implementation Cell 1 to 8 and Comparative Cell 1 to 9.
[0087]
[0088]
[0089] As can be seen from Table 1, in the electrode assemblies 110 of Examples 1 to 8, Comparative Examples 1 to 4, and Comparative Examples 6 to 8, the diaphragm 112 is a polyethylene base film 1121, and a ceramic coating 1122 is coated on the surface of the base film 1121. In Comparative Example 5, the diaphragm 112 includes only the polyethylene base film 1121.
[0090] Testing of performance parameters of implementation battery 1 to implementation battery 8 and comparison battery 1 to comparison battery 9:
[0091] 1. Impedance test of battery 100:
[0092] The battery was charged to 3.65V at 0.5C, then charged to 0.05C at 3.65V constant voltage, and left at 25℃ for 30min. Discharged at 0.1C for 1h, left at rest for 60min, and the voltage V1 after rest was recorded. Then, it was discharged at 1.07C for 30s, with a sampling interval of 30s, and the voltage V2 at the end of discharge was recorded. The battery DCR (DC internal resistance) = (V1-V2) / I, I = 1.07C. Left at rest for 40s, then charged at 1.07C constant current for 30s, and left at rest for 10min. This cycle was repeated 9 times, and the discharge DCR at 50% SOC was recorded.
[0093] Wherein, SOC is the abbreviation of "State of Charge", which represents the remaining power or charging state of the battery 100, and is used to describe the amount of charge that has been charged in the battery 100 relative to the total capacity of the battery 100. 50% SOC means that the remaining power of the battery 100 is 50% of the total capacity of the battery 100. The values of the DC internal resistance DCR of the implementation battery 1 to the implementation battery 8 and the comparison battery 1 to the comparison battery 9 are shown in Table 2.
[0094] 2. Cycle performance test of battery 100:
[0095] (1) Initialization discharge: Under 25°C environment, let implementation battery 1 to implementation battery 8 and comparison battery 1 to comparison battery 9 stand for 2 hours; step 1: charge battery 100 to 3.65V at a rate of 0.5P; step 2: let stand for 30 minutes; step 3: discharge battery 100 to 2.5V at a rate of 0.5P; step 4: let stand for 30 minutes; step 5: repeat step 1 → step 2 → step 3 → step 4 three times to complete the initialization charge and discharge.
[0096] (2) 25℃ 0.5P cycle: In an environment of 25℃, the battery 100 that has completed the initial discharge is allowed to stand for 2 hours; Step 1: Charge the battery 100 to 3.65V at a rate of 0.5P; Step 2: Allow to stand for 30 minutes; Step 3: Discharge the battery 100 to 2.5V at a rate of 0.5P; Step 4: Allow to stand for 30 minutes; Step 5: Record the discharge capacity of the first cycle of the battery 100 as C1.
[0097] The cycle performance test was carried out according to the above-mentioned charge and discharge process (first step → second step → third step → fourth step → fifth step), and the discharge capacity C2 of the battery 100 after completing 500 charge and discharge cycles at a rate of 0.5P at 25°C was recorded to obtain the discharge capacity retention rate K1 of the battery 100 relative to the initial capacity, wherein K1=C2 / C1. The values of the discharge capacity retention rate K1 of the implementation battery 1 to the implementation battery 10 and the comparison battery 1 to the comparison battery 9 after 500 cycles at a rate of 0.5P at 25°C are shown in Table 2.
[0098] (3) 45℃ 1P cycle: In a 45℃ environment, the battery 100 that has completed the initial charge and discharge is left to stand for 2 hours; Step 1: Charge the battery 100 to 3.65V at a 1P rate; Step 2: Leave it to stand for 30 minutes; Step 3: Discharge the battery 100 to 2.5V at a 1P rate; Step 4: Leave it to stand for 30 minutes; Step 5: Record the discharge capacity of the first cycle of the battery 100 as C3.
[0099] According to the above-mentioned charge and discharge process (first step → second step → third step → fourth step → fifth step), a cycle performance test was performed, and the discharge capacity C4 of the battery 100 after completing 500 charge and discharge cycles at a rate of 1P at 45°C was recorded to obtain the discharge capacity retention rate K2 of the battery 100 relative to the initial capacity, wherein K2=C4 / C3. The values of the discharge capacity retention rate K2 of the implementation battery 1 to the implementation battery 10 and the comparison battery 1 to the comparison battery 9 after 500 cycles at a rate of 1P at 45°C are shown in Table 2.
[0100] It can be understood that the discharge capacity retention rate K1 of 500 cycles at 0.5P rate at 25°C can characterize the cycle performance of the battery 100 under normal temperature environment, and the capacity retention rate of 500 cycles at 1P rate at 45°C can characterize the cycle performance of the battery 100 under high temperature environment.
[0101] Table 2: Performance parameters of implementation batteries 1 to implementation batteries 8 and comparative batteries 1 to comparative batteries 9.
[0102]
[0103] Please refer to Table 1 and Table 2. From the data of Examples 1 and 2, Examples 4 and 5 and Comparative Example 1, it can be seen that the electrolyte 120 in Examples 1 and 2, and Examples 4 and 5 all include the first additive and the second additive, and the mass fraction a of the first additive, the mass fraction b of the second additive, and the value of b / a are all within a reasonable range. The electrolyte 120 of Comparative Example 1 does not include the first additive or the second additive, so that the DC internal resistance DCR of the implementation battery 1 to the implementation battery 2, the implementation battery 4 and the implementation battery 5 at 50% SOC discharge is less than the DC internal resistance DCR of the comparative battery 1 at 50% SOC discharge, the capacity retention rate K1 of the implementation battery 1 to the implementation battery 2, the implementation battery 4 and the implementation battery 5 at 25°C and 1P rate for 500 cycles is higher than the capacity retention rate K1 of the comparative battery 1 at 0.5P rate for 500 cycles at 25°C, and the implementation battery 1 and the implementation battery 2 are 1P and 5 ... The capacity retention rate K2 of battery 2, implementation battery 4 and implementation battery 5 after 500 cycles at 1P rate at 45°C is higher than the capacity retention rate K2 of comparison battery 1 after 500 cycles at 1P rate at 45°C. In addition, this shows that the electrolyte 120 of this embodiment, through the synergistic effect of the first additive and the second additive, makes the SEI film formed by the first additive on the surface of the negative electrode plate 111 have good stability, so as to avoid decomposition or structural damage of the SEI film, reduce the consumption of active lithium in the electrolyte 120, reduce the internal resistance of the battery 100 under high temperature conditions, and avoid the attenuation of the capacity of the battery 100, so that when the electrolyte 120 is applied to the battery 100, the battery 100 has higher energy efficiency, better cycle performance and safety performance. Compared with the capacity retention rate of the battery 100 at 25°C, the capacity retention rate of the battery 100 at high temperature is reduced to a certain extent, but still maintains a higher capacity retention rate. Further, in Examples 1 and 2, as well as Examples 4 and 5, as the mass fraction of the first additive and the mass fraction of the second additive increase, the electrolyte 120 can form a complete, thermally stable, and highly conductive SEI film on the surface of the negative electrode plate 111. Accordingly, by increasing the amount of doping elements in the active material layer 1132, the battery 100 can maintain a relatively high capacity retention rate under high temperature conditions. The electrolyte 120 and the positive electrode plate 113 cooperate with each other, which is beneficial to improving the energy efficiency of the battery 100. Among them, in Example 4, when the mass fraction a of the first additive is 2%, the mass fraction of the second additive is 2%, and x is 0.03, the internal resistance of the battery 100 is small, and the capacity retention rate of the battery 100 is high, and it has good cycle performance.
[0104] Further, please refer to Example 3 and Comparative Examples 2 to 4. It can be seen from the data of Example 4 and Comparative Example 2 that the mass fraction of the first additive, the mass fraction of the second additive and the value of a / x of Comparative Example 2 are too large, so that the DC internal resistance DCR of Comparative Battery 2 at 50% SOC discharge is greater than the DC internal resistance DCR of Implementation Battery 4 at 50% SOC discharge, and the capacity retention rate of Comparative Battery 2 at 25°C at a rate of 0.5P for 500 cycles is much lower than the capacity retention rate of Implementation Battery 4 at 45°C at a rate of 1P for 500 cycles, and the capacity retention rate of Comparative Battery 2 at 45°C at a rate of 1P for 500 cycles is much lower than the capacity retention rate of Implementation Battery 4 at 45°C at a rate of 1P for 500 cycles. The capacity retention rate of the implemented battery 4 is 500 cycles at 1P rate at 45°C. This is because: if the mass fraction of the first additive is too large, the thickness of the SEI film formed by the first additive on the surface of the negative electrode plate 111 is too large, which increases the resistance of lithium ions in the electrolyte 120 to embed or escape from the SEI film. If the mass fraction of the second additive is too large, it may inhibit the first additive from forming a SEI film on the surface of the negative electrode plate 111, resulting in the first additive being unable to form a stable and complete SEI film on the surface of the negative electrode plate 111, thereby reducing the stability of the electrolyte 120 under high temperature conditions. From the data of Example 3 and Comparative Example 3, it can be seen that, under the same other conditions, the values of x and a / x in Example 3 are within a reasonable range, while the value of x in Comparative Example 3 is too small, which makes the value of a / x too large, so that the DC internal resistance DCR of the comparative battery 3 at 50% SOC discharge is greater than the DC internal resistance DCR of the implementation battery 3 at 50% SOC discharge, and the capacity retention rate of the comparative battery 3 at 45°C at a 1P rate for 500 cycles is less than the capacity retention rate of the implementation battery 3 at 45°C at a 1P rate for 500 cycles. This is because: in LiM x Fe (1-x) In PO4, the amount of doping elements is too small, so that the efficiency of lithium ion embedding or extraction from the positive electrode plate 113 is low. In other words, the impedance of the lithium ion extraction from the active material layer 1132 is large. Correspondingly, the lithium ions diffused from the active material layer 1132 are too small. Even if the SEI film formed by the first additive and the second additive on the surface of the negative electrode plate 111 has a high ionic conductivity, it is difficult to improve the energy efficiency and capacity retention rate of the battery 100. Similarly, from the data of Example 3 and Comparative Example 4, it can be seen that under the same other conditions, the value of x in Comparative Example 4 is too large, so that the value of a / x is too small, so that the DC internal resistance DCR of the comparative battery 4 at 50% SOC discharge is greater than the DC internal resistance DCR of the implementation battery 3 at 50% SOC discharge, and the capacity retention rate of the comparative battery 4 at 45°C at a 1P rate for 500 cycles is less than the capacity retention rate of the implementation battery 3 at 45°C at a 1P rate for 500 cycles. This is because: in LiM x Fe(1-x) In PO4, the amount of doping elements is too much, which makes the efficiency of lithium ions embedding or extracting from the positive electrode plate 113 too high. Correspondingly, too many lithium ions diffused from the active material layer 1132 are over-consumed, thereby reducing the amount of reversible lithium ions in the battery 100 and ultimately reducing the capacity retention rate of the battery 100.
[0105] Please refer to Example 3, Example 6 to Example 8, and Comparative Example 6 to Comparative Example 7. It can be seen from the data of Example 3, Example 6 to Example 8, and Comparative Example 6 to Comparative Example 8 that, under the same other conditions, the electrolyte 120 of Example 3, Example 6 to Example 8 all include the first additive and the second additive, and the mass fraction b and b / a values of the second additive are both within a reasonable range, while the electrolyte 120 of Comparative Example 6 does not include the second additive, the mass fraction and b / a values of the second additive in the electrolyte 120 of Comparative Example 7 are both too large, and the b / a value in the electrolyte 120 of Comparative Example 8 is too small, so that the DC internal resistance DCR of Comparative Battery 6 to Comparative Battery 8 at 50% SOC discharge is greater than that of Example 3, Example 6 to Example 8 at 50% SOC discharge. The DC internal resistance DCR at 50% SOC discharge, the capacity retention rate of comparison battery 6 to comparison battery 8 after 500 cycles at 0.5P rate at 25°C is less than that of implementation battery 3, implementation battery 6 to implementation battery 8 after 500 cycles at 0.5P rate at 25°C, and the capacity retention rate of comparison battery 6 to comparison battery 8 after 500 cycles at 1P rate at 45°C is less than that of implementation battery 3, implementation battery 6 to implementation battery 8 after 500 cycles at 1P rate at 45°C. This is because: when the electrolyte 120 includes the first additive and the second additive, the second additive can combine with the proton hydrogen of the first additive to form trimethylfluorosilane to avoid the generation of hydrogen fluoride, thereby further improving the stability of the SEI film formed by the first additive. Furthermore, the phosphate group of the second additive can also form a product with the lithium ions in the electrolyte 120, which is beneficial to increase the thickness of the SEI film, thereby further improving the stability of the SEI film. The electrolyte 120 of this embodiment has a synergistic effect of the first additive and the second additive, so that the SEI film formed by the first additive on the surface of the negative electrode plate 111 has good stability, so as to avoid decomposition or structural damage of the SEI film, reduce the consumption of active lithium in the electrolyte 120, reduce the internal resistance of the battery 100 under high temperature conditions, and avoid the attenuation of the capacity of the battery 100, so that when the electrolyte 120 is applied to the battery 100, the battery 100 has higher energy efficiency, better cycle performance and safety performance. However, if the mass fraction of the second additive is too large, the first additive is inhibited from forming a SEI film on the surface of the negative electrode plate 111, so that the stability of the electrolyte 120 under high temperature conditions deteriorates, and the capacity retention rate of the battery 100 is reduced. In addition, if the value of b / a is too small, the second additive cannot fully combine with the proton hydrogen detached from the first additive, and some of the proton hydrogen may react with the electrolyte 120 to generate hydrogen fluoride and attack the SEI film formed by the first additive, thereby reducing the structural stability of the solid electrolyte interface film, thereby causing the capacity retention rate of the battery 100 to be low in a high temperature environment.
[0106] Please refer to Example 3, Comparative Example 5 and Comparative Example 9. It can be seen from the data of Example 3, Comparative Example 5 and Comparative Example 9 that, under the same other conditions, the diaphragm 112 of Example 3 includes the coating 1122 and the coating 1122 is a boehmite coating, the diaphragm 112 of Comparative Example 5 only includes the polyethylene base film 1121, and the diaphragm 112 of Comparative Example 5 includes the polyethylene base film 1121, but the surface of the polyethylene base film 1121 is an aluminum oxide coating, so that the comparative battery 5 and the comparative battery 9 have the same thickness. The DC internal resistance DCR at 0% SOC discharge is greater than the DC internal resistance DCR of the implementation battery 3 at 50% SOC discharge. The capacity retention rate of the comparative battery 5 and the comparative battery 9 after 500 cycles at 0.5P rate at 25°C is much lower than the capacity retention rate of the implementation battery 3 after 500 cycles at 0.5P rate at 25°C. The capacity retention rate of the comparative battery 5 and the comparative battery 9 after 500 cycles at 1P rate at 45°C is much lower than the capacity retention rate of the implementation battery 3 after 500 cycles at 1P rate at 45°C. This shows that: when the diaphragm 112 includes a base film 1121 and a coating 1122, and the coating 1122 is a boehmite coating, the coating 1122 has hydroxyl groups. When the diaphragm 112 and the first additive are used in combination, the proton hydrogen on the five-membered heterocyclic ring of the first additive is easily combined with the hydroxyl group due to the action of hydrogen bonds, so that the first additive is easily adsorbed on the surface of the coating 1122. The nitrogen atoms in the first additive contain lone pairs of electrons, which can attract lithium ions in the electrolyte 120 and make the lithium ions pass through the diaphragm 112 quickly, so as to reduce the impedance of the lithium ions passing through the diaphragm 112. The diaphragm 112 has higher thermal conductivity and higher ionic conductivity. During the charge and discharge process of the battery 100, the diaphragm 112 can effectively transfer the heat generated by the electrode assembly 110 to the outside, so as to avoid the problem of thermal runaway caused by excessive heat inside the battery 100, thereby further improving the safety performance of the battery 100. Correspondingly, the surface of the coating 1122 in Comparative Examples 5 and 9 is not provided with a boehmite coating, thereby weakening the thermal conductivity and ionic conductivity of the diaphragm 112, so that the DC internal resistance DCR of Comparative Battery 5 and Comparative Battery 9 at 50% SOC discharge is larger, and the capacity retention rate at 25°C, 0.5P rate, and 500 cycles at 45°C, 1P rate, is low.
[0107] See also Figure 4 and Figure 5 The present application provides an electrical device 200 , which includes: a device body 210 and a battery 100 provided in the present application, and the battery 100 supplies power to the device body 210 .
[0108] It can be understood that the battery 100 is electrically connected to the device body 210 .
[0109] In this embodiment, the battery 100 has high energy efficiency, good cycle performance and safety performance, so that the battery 100 can provide stable power for the device body 210, which is beneficial to improving the user experience.
[0110] Optionally, the power-consuming device 200 of the embodiment of the present application may be, but is not limited to, a portable electronic device such as a mobile phone, a tablet computer, a laptop computer, a desktop computer, a smart bracelet, a smart watch, an e-reader, a game console, etc. It may also be a vehicle such as a car, a truck, a car, a truck, a truck, a motor vehicle, a high-speed train, an electric vehicle, etc. In addition, it may also be various household appliances, etc. The present application Figure 5 The electrical equipment 200 of the embodiment is an energy storage battery cabinet.
[0111] It can be understood that the electrical equipment 200 described in this embodiment is merely a form of the electrical equipment 200 used by the sodium ion battery 100, and should not be understood as a limitation on the electrical equipment 200 provided in the present application, nor should it be understood as a limitation on the electrical equipment 200 provided in each embodiment of the present application.
[0112] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, provided that there is no contradiction between them.
[0113] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.
Claims
1. An electrolyte, characterized in that: The electrolyte includes a first additive and a second additive, wherein the first additive includes 2,3-dihydropyrido[2,3-d][1,3]oxazol-2-one, and the second additive includes tris(trimethylsilyl)phosphate.
2. The electrolyte according to claim 1, characterized in that In the electrolyte, the mass fraction of the first additive is a, and the mass fraction of the second additive is b, and the relationship is satisfied: 0.4≤b / a≤4.
3. The electrolyte according to claim 1, characterized in that The mass fraction a of the first additive is in the range of 0.1%≤a≤5%.
4. The electrolyte according to claim 1, characterized in that In the electrolyte, the mass fraction b of the second additive is in the range of 0.1%≤b≤5%.
5. A battery, characterized in that: The battery comprises: An electrode assembly, the electrode assembly comprising a stacked negative electrode sheet, a separator and a positive electrode sheet, the positive electrode sheet comprising a stacked current collector layer and an active material layer; and The electrolyte according to any one of claims 1 to 4, wherein the electrolyte is used to wet at least a portion of the electrode assembly.
6. The battery according to claim 5, characterized in that The active material layer includes LiM x Fe (1-x) PO4, wherein M is selected from at least one of vanadium, titanium, magnesium, manganese, aluminum and molybdenum, and the range of x is: 0.005≤x≤0.
05.
7. The battery according to claim 6, characterized in that In the electrolyte, the mass fraction of the first additive is a, and the battery satisfies the relationship: 0.2≤a / x≤1.
8. The battery according to claim 5, characterized in that The diaphragm includes a base film and a coating layer which are stacked, the coating layer is a ceramic coating and the thickness D of the coating layer satisfies the range of 2.5 μm≤D≤3.5 μm.
9. The battery according to claim 8, characterized in that The coating has pores, and the porosity α of the coating is in the range of 35%≤α≤65%.
10. An electrical device, characterized in that: The electrical equipment includes: Equipment body; The battery according to any one of claims 5 to 9, wherein the battery is used to power the device body.
Citation Information
Patent Citations
Silyl-containing oxazolidinone lithium ion battery electrolyte and battery
CN113363576A
Lithium secondary battery electrolyte and lithium secondary battery
CN114094189A
Electrolyte additive, electrolyte, battery and electric device
CN117525590A
Anti-overcharge electrolyte and lithium ion battery using same
CN117638225A
Scent and Sound Diffuser for Alleviating Pet Separation Anxiety
KR1020260063068A